A case for decolonizing English language instruction. (3rd December 2019) - Meighan, Paul J
Abstract: Comment is a feature that allows contributors to express a personal, and sometimes controversial, view about a matter of current concern in the profession outside the format of a reviewed academic article. The views expressed are not necessarily those of the Editor or the Publisher. Reaction to Comment features, in the form of letters to the Editor, are especially welcome.